2023
DOI: 10.1007/s10554-023-02893-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve regurgitation assessed by intraventricular CMR 4D-flow: a systematic review on the technological aspects and potential clinical applications

Abstract: Cardiac magnetic resonance (CMR) four-dimensional (4D) flow is a novel method for flow quantification potentially helpful in management of mitral valve regurgitation (MVR). In this systematic review, we aimed to depict the clinical role of intraventricular 4D-flow in MVR. The reproducibility, technical aspects, and comparison against conventional techniques were evaluated. Published studies on SCOPUS, MEDLINE, and EMBASE were included using search terms on 4D-flow CMR in MVR. Out of 420 screened articles, 18 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is suitable for MR assessment also in concomitant valvular pathologies or shunt flows, but has been shown to be less reproducible in primary MR, mainly due to the complex and time-consuming plane reformatting process [ 27 ]. Based on a recent systematic review, more than 80% of recent studies have shown that the 4D flow analysis technique calculating mitral inflow and aortic forward flow for the MR RVol calculation exhibited the best inter- and intra-observer reproducibility [ 33 ]. All standard and novel methods for RVol quantification, summarized in the table below, can be used in routine practice for cross-validating, aiming for a comprehensive and robust assessment of the severity of MR.…”
Section: How To Assess Mitral Regurgitation With Cmrmentioning
confidence: 99%
“…It is suitable for MR assessment also in concomitant valvular pathologies or shunt flows, but has been shown to be less reproducible in primary MR, mainly due to the complex and time-consuming plane reformatting process [ 27 ]. Based on a recent systematic review, more than 80% of recent studies have shown that the 4D flow analysis technique calculating mitral inflow and aortic forward flow for the MR RVol calculation exhibited the best inter- and intra-observer reproducibility [ 33 ]. All standard and novel methods for RVol quantification, summarized in the table below, can be used in routine practice for cross-validating, aiming for a comprehensive and robust assessment of the severity of MR.…”
Section: How To Assess Mitral Regurgitation With Cmrmentioning
confidence: 99%
“… 65 , 66 New advances in 4D flow cardiac magnetic resonance imaging are growing, and potentially will be helpful in the future management of mitral valve regurgitation. 67 …”
Section: Evaluation Of the Mitral Valve Apparatus In Cardiomyopathiesmentioning
confidence: 99%